Türkmenistan ahal bölgesi coğrafi etüdü - Koşak, Fatih (My University, 2007)
97.210 km²’lik bir alana sahip olan Ahal Bölgesi, Orta Asya’daki Türk ülkelerinden Türkmenistan’ın güney ve güneybatı kesimlerini içine alır. 35º30' ve 40º13' kuzey enlemleri ile 56º35' ve 61º38' doğu boylamları arasındadır. Ahal Bölgesi, geçmişte önemli geçiş güzergâhlarında yer alırken günümüzde ekonomik olarak büyük potansiyellere sahiptir. Bölge yeryüzü şekilleri yönünden çok sade bir görünüm arz eder. Karasal çöl iklimine sahip bölgede yağış son derece az görülür. Yağışın az olması suya olan ihtiyacı çok öne çıkarmış ve bu yüzden dünyanın en büyük yapay su kanalı olan Karakum Kanalı’nın yapımı gerçekleştirilmiş ve üzerinde sulama amaçlı barajlar yapılmıştır. Karakum Kanalı sulama maksadı ile yapılan en büyük kanaldır. Kopet dağlarının bölgenin fiziki şartlarının oluşumuna önemli etkileri vardır. Alp-Himalaya sisteminin bir parçası olan Kopet dağları aşınmış ve çıplak yüzeyleriyle dikkat çeker. Kopet dağlarının Ahal içerisinde kalan batı bölümü 2000–3000 m yüksekliklerden Türkmenistan’ın düzlük sahasına dimdik iner. Dağların çöl sahasıyla kesiştiği bölgede dağ sırasıyla aynı doğrultuda uzanan büyük bir fay hattı vardır. Dünyanın en önemli çöllerinden biri olan Karakum çölünün bir kısmı bölge içerisinde kalır. Kumlarla örtülmüş çöl sahasının dışında boz topraklar, alüvyal topraklar ve lösler önemli yer tutar. Genel olarak fakir olan bitki örtüsü gür ve çeşitli değildir. Bölgede hâkim olan ekonomik faaliyet tarım ve hayvancılık ile sanayi sektörüdür. Sanayi sektöründe her geçen gün gelişmeler görülmektedir. Bölge tarihi olarak da en eski medeniyetlere ev sahipliği yapmıştır. Yöre de yöresel giyim ön plana çıkmaktadır. Türkmen halıları ve Ahal-Teke atları dünyaca meşhurdur. Türkmenistan’da nüfusun en yoğun olduğu bölge olan Ahal, 2005 yılı sayımına göre 1,800.000’i aşkın bir nüfusa sahiptir. Ülkeye göre nüfus yoğunluğunun fazla olmasında başşehir Aşkabat’ın etkisi büyüktür. Ulaşımda karayolu, demiryolu ve hava yolu kullanılır. Suyolu ile yük taşımacılığı da yapılmaktadır. Bölge, Türkmenistan’da ticaretin en yoğun yapıldığı merkez konumundadır. Bir doğalgaz üreticisi olan Türkmenistan’ın önemli doğalgaz yatakları Ahal Bölgesi’nde yer alır. Bölge turizm açısından da önemli özelliklere sahiptir. Bölgenin her alanda tanıtımı yaygınlaştırıldığında önemi daha da artacaktır.

Ahal is a region of 97.210 km² of Turkmenistan which is among the Turkish countries located in the Middle Asia, and contains the south and southwest parts of Turkmenistan. It’s between 35º 30' and 40º 13' north latitudes with 56º 35' and 61º 38' east longitudes. Ahal Region was located on the critical place of passages in the past, but nowadays it has big economical potential. The region shows a very simple view concerning the land shapes. Extremely little rain is observed in this region which has continental desert climate. Therefore, there is an utmost need for water, so Karakum Channel is built which is the biggest artificial water channel in the world. On this channel, barrages are built for watering purposes. Karakum Channel is the biggest channel built for watering. Kopet mountains effect the physical characteristics of the region. These mountains, which are a part of the Alp-Himalaya system, appear with the worn and naked surfaces. The west part of Kopet mountains inside Ahal Region straightly lies down from the heights of 2000-3000 m to the plain surfaces of Turkmenistan. In the intersection of mountains with the desert area, there is a big line of fault which lies down parallel with the mountain rows. Some parts of Karakum desert, which is among the most important deserts in the world, are contained in this region. Besides the desert area covered by sands, there are rough lands, alluvial lands and dusty lands. Generally the plants are poor, not several and well-growed.Economical activities in this region are agriculture, animal husbandry and sector of industry. Improvements have been made in the sector of industry. Historically, the region has hosted the oldest civilizations. In the region, local clothing is very important. Turkoman carpets and horses of Ahal-Teke are very famous. Ahal is the most populated region in Turkmenistan and it has a population of 1.800.000 as per 2005. The capital city Ashkhabad is very effective on the high population of the country.Transportation is made by land, rail and air ways. Load transportation is also made by water lines. The region is the trade center in Turkmenistan.In Turkmenistan which is a producer of natural gas, the important natural gas beds are located in Ahal Region. This region has very important characteristics for tourism. When the recognition of the region is widespread in every field, the region will gain more importance in the future. Sayfa ÖZET. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . I SUMMARY. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .II ÖNSÖZ . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . III LLER LİSTESİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .IX TABLOLAR LİSTESİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . X GRAFİKLER LİSTESİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . XII FOTOĞRAFLAR LİSTESİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . XIII GİRİŞ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 1 ARAŞTIRMANIN AMACI VE METODU . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 2 ARAŞTIRMA SAHASININ KONUMU, SINIRLARI, GENEL ÖZELLİKLERİ. . . . . . . . 3 RAFYA ÖZELLİKLERİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .6 1.1. JEOLOJİK VE JEOMORFOLOJİK ÖZELLİKLER. . . . . . . . . . . . . . . . . . . . .6 1.2. İKLİM ÖZELLİKLERİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .11 1.2.1. Sıcaklık. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 13 1.2.2. Yağış ve Nemlilik. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 14 1.2.3. Basınç Şartları ve Rüzgâr. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 16 1.3. HİDROGRAFYA ÖZELLİKLERİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .18 1.3.1 Tecen Nehri. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 19 1.3.2. Karakum Kanalı. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .20 1.3.3. Kaynağını Kopetdağ’dan alan küçük akarsular. . . . . . . . . . . . . . . . . .21 1.3.4. Yeraltı Suları . . . . . . . . . . . . . . . . . . . . . . . . . . . . .. . . . . . . . . . . . . . . . . 21 1.4. TOPRAK ÖZELLİKLERİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 24 1.4.1. Düzlük Sahaların Toprakları. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 24 1.4.1.1. Takır Görünüşlü Topraklar. . . . . . . . . . . . . . . . . . . . . . . . . . .25 1.4.1.2. Takır Topraklar. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 25 1.4.1.3. Çayır toprakları. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 25 1.4.1.4. Tuzlu Topraklar. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .26 1.4.2. Dağlık Yerlerin Toprakları. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 26 1.4.2.1. Esmer Renkli Topraklar. . . . . . . . . . . . . . . . . . . . . . . . . . . . . .27 1.4.2.2. Tipik Esmer Topraklar. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .27 1.4.2.3. Açık Kestane Renkli Topraklar. . . . . . . . . . . . . . . . . . . . . . . .27 1.5. BİTKİ ÖRTÜSÜ ÖZELLİKLERİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 29 1.5.1. Çöl Vejetasyonu. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 30 1.5.2. Dağlık Alanların Vejetasyonu. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .32 1.5.3. Vaha Vejetasyonu. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .35 1.5.4. Akarsu Vejetasyonu. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .35 1.6. DOĞAL YAPIYLA İLGİLİ ÇALIŞMALAR. . . . . . . . . . . . . . . . . . . . . . . . . . . 37 İKİNCİ BÖLÜM 2. BEŞERİ COĞRAFYA ÖZELLİKLERİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .38 2.1. BÖLGENİN TARİHÇESİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 38 2.2. BÖLGENİN YERLEŞME ÖZELLİKLERİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . 44 2.2.1. Bölgenin Yerleşme Tarihi ve Meskenler. . . . . . . . . . . . . . . . . . . . . . . . 45 2.3. NÜFUS. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .49 2.3.1. Nüfus Miktarları, Değişimleri ve Nedenleri. . . . . . . . . . . . . . . . . . . . . 51 2.3.2. Ahal Bölgesinin Nüfus Dağılımı. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .54 2.3.3. Nüfus Yoğunluğu. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 56 2.3.4. Köy ve Şehir Nüfusu. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 57 2.3.5. Nüfusun Cinsiyet Durumu. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 61 2.3.6. Nüfusun Eğitim Durumu ve Eğitim Olanakları. . . . . . . . . . . . . . . . . . 61 2.3.7. Etnik yapı. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 64 2.4. BÖLGENİN KÜLTÜREL ÖZELLİKLERİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . 67 2.4.1. Mücevherat ve Takı Sanatı. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .67 2.4.2. Giyim Kuşam. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .68 2.4.3. Türkmen Halıları. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .69 2.4.4. Ahal-Teke ve Yomut Atları. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 70 2.4.5. Din ve İnanış. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 71 2.4.6. Kutlamalar(Toylar) . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 71 2.4.7. Bölge Mutfağı. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .72 2.4.8. Bayramlar. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 72 2.4.9. Türkmen Evi. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 73 2.4.10. Türkmen Folkloru. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .73 ÜÇÜNCÜ BÖLÜM 3. EKONOMİK COĞRAFYA ÖZELLİKLERİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 74 3.1. TARIM ve HAYVANCILIK. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .76 3.1.1. Tarım. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 76 3.1.1.1. Tahıl ve Baklagillerin Üretimi. . . . . . . . . . . . . . . . . . . . . . . . .78 3.1.1.2. Pamuk Üretimi. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .79 3.1.1.3. Sebzecilik ve Bahçecilik. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 81 3.1.1.4. Bağcılık ve Meyvecilik. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 82 3.1.1.5. Yem Bitkileri Üretimi. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .83 3.1.2. Hayvancılık. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .84 3.1.2.1. Koyunculuk. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .84 3.1.2.2. Sığırcılık. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .85 3.1.2.3. Deve Yetiştiriciliği. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .86 3.1.2.4. At Yetiştiriciliği. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .87 3.1.2.5. Kümes Hayvancılığı. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 87 3.1.2.6. İpek Böcekçiliği. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .88 3.1.2.7. Balıkçılık. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 88 3.1.2.8. Arıcılık. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .88 3.2. SANAYİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .90 3.2.1. Makine Sanayisi. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .93 3.2.2 Yem Sanayisi. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .94 3.2.3. Enerji Üretim Tesisleri. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 94 3.2.4. Kimya Sanayisi. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .94 3.2.5. Yapı Malzemeleri Sanayisi. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 95 3.2.6. Gıda Sanayisi. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 96 3.2.7. Hafif Sanayi. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 97 3.3. YERALTI KAYNAKLARI. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .99 3.4. TİCARET. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .104 3.5. ULAŞIM. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .106 3.6. TURİZM. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .111 DÖRDÜNCÜ BÖLÜM 4. ARAŞTIRMA SAHASININ TEMEL SORUNLARI VE BAŞLICA ÇÖZÜM ÖNERİLERİ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .113 SONUÇ. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .116 EKLER. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .118 FAYDALANILAN KAYNAKLAR. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 190
Keywords: Coğrafya_Türkmenistan; Coğrafya, Fiziksel_Türkmenistan